1961
DOI: 10.1107/s0365110x61002540
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of diaquabis(salicylaldehydato)nickel

Abstract: The crystal structure of diaquabis (salicylaldehydato) nickel has been determined by 2-dimensional projections. The cell dimensions are ao=12.93, b 0=7.32, c0=7.41,~, fl=90°15 ', Z=2.The space group is A2/m. The molecule has a trans octahedral configuration with Ni-O distances 2.03 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1965
1965
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 1 publication
1
22
0
1
Order By: Relevance
“…Surprisingly, no reaction occurred with nickel acetate, presumably because of the steric hindrance induced by the PPh 3 group. In order to avoid this problem, we tried in this case also to invert the order of the reactions, i.e., to use the preformed Ni(Salen) 2 AE 2H 2 O complex [20] in a condensation reaction with 2. After 5 days at 60°C, the dark green paramagnetic solution of 8 and 2 becomes a yellow diamagnetic solution of 9b (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, no reaction occurred with nickel acetate, presumably because of the steric hindrance induced by the PPh 3 group. In order to avoid this problem, we tried in this case also to invert the order of the reactions, i.e., to use the preformed Ni(Salen) 2 AE 2H 2 O complex [20] in a condensation reaction with 2. After 5 days at 60°C, the dark green paramagnetic solution of 8 and 2 becomes a yellow diamagnetic solution of 9b (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…Solvents were dried and distilled prior to use (THF and ether over sodium/benzophenone, pentane and CH 2 Cl 2 over phosphorus pentoxide) and degazed when phosphines are used. Compounds 1 [11], 6 [20] and AuCl(tht) [21] were prepared as described previously.…”
Section: Generalmentioning
confidence: 99%
“…Ab initio phase and amplitude functions for Ni-O, Ni-Fe, Ni-Mn, and Ni-Al were generated from the refinement of hydrotalcite where Ni, Fe, or Mn were substituted for Mg in the octahedral layer, and from the structures of Trevorite ð½ðNi; CuÞFe 2 3þ O 4 Þ, Heazlewoodite (Ni 3 S 2 ), Godlevskite ((Ni 8.7 ,Fe 0.3 ) 9 S 8 ), and Gaspeite ((Ni,Mg,Fe)CO 3 ). The Ni-O and Ni-C (organic acids) phase and amplitude functions were generated using either nickel acetate tetrahydrate ((Ni(CH) 3 COO) 2 H 2 O) (Nicolai et al, 1998) or disaguabis(salicyladehydato) nickel (Ni(sal) 2 (H 2 O) 2 ) (Stewart et al, 1961) and Ni-N (amino acids) paths using Ni-Imidazole (C 3 H 4 N 2 ) 6 Ni(NO 3 ) 2 (Santoro et al, 1969). The parameters obtained fitting the individual shells were then refined using a multi-shell fit over the entire spectra in k space (Dk = 2.1-10.8).…”
Section: Bulk Xafs Standard Preparation Data Collection and Charactementioning
confidence: 99%
“…Complexes of Ni H with ligands such as aminocyclohexanecarboxylate (Haendler, 1993), hexafluoroacetonate (Polam & Porter, 1992), salicyaldehydate (Stewart, Lingafelter & Breazeale, 1961), acetylacetonate and tetramethylethylenediamine (Yamada, Hori & Fukuda, 1993), benzenedicarboxylate and 2,2'-bipyridyl (Poleti, Karanovic & Prelesnik, 1990), glycinate and 2,2'-bipyridyl (Z~ik, Gtowiak, Kamenffzek & B~ezina, 1990), carboxylates and silane carboxylate (Morooka et al, 1992) have been reported. Although the structure of flavonol chelated to copper has been reported (Speier, Fiilop & Parkanyi, 1990), little information is available on the analogues of nickel.…”
Section: Commentmentioning
confidence: 99%